The piglet acute diarrhea model for evaluating efficacy of treatment and control of cryptosporidiosis. Issue 6 (3rd June 2019) - Lee, Sangun; Beamer, Gillian; Tzipori, Saul
ABSTRACT: Cryptosporidium spp. are ranked as the second leading pathogens causing life-threatening diarrhea in children under 2 years of age. Although Cryptosporidium hominis causes three quarters of the cases of cryptosporidiosis, studies on C. hominis are limited since natural disease due to C. hominis is host-restricted to humans only. In this mini-review, we demonstrate the successfully adoption, propagation, and utility of the C. hominis strain TU502, isolated originally from an infant with diarrhea in Uganda, in gnotobiotic piglets. The TU502 C. hominis strain and the gnotobiotic piglet model currently are the only available preclinical tools to evaluate therapeutics that specifically target C. hominis . Infection in this gnotobiotic piglet model displays similar clinical symptoms of diarrhea observed in humans. Here we further describe how this unique model of acute diarrhea, can be used for drug discovery and testing of vaccine candidates against cryptosporidiosis. The shared anatomical, physiological and immunological characteristics between piglets and human infants makes the model ideal for evaluating the efficacy of therapeutics and vaccines against cryptosporidiosis as they become available.